Internet defamation litigation. Comments on the SAP Madrid 10 February 2023: Jurisdiction and applicable Law, is silence worth a thousand words? - Recuenco Pérez, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Defamation litigation on the Internet is more complex than in traditional media. Among other things, because defamatory content can be accessible from anywhere in the world. The ubiquity of these torts affects important issues of private international law. For example, the plaintiff has up to four choices of forum. It depends on this choice whether the court can hear all damages suffered in the world or whether it can only decide on damages caused in its territory. In addition, the choice of the competent court, according to one forum or another, will condition the judge to estimate or dismiss the actions for injunctive. Therefore, the court of the country where the complainant decides to sue, must apply its own conflict rule to determine the applicable law to the merits of the case. This law will resolve issues such as active legitimacy or expiration of the action. The decision under comment does not address these issues. When it does, it does so erroneously.
Keywords: Internet defamation; non-contractual obligations; Art 7.2 Brussels Ia Regulation; Art 10.9.I CC; victim’s center of main interests